Utility of Sequential Organ Failure Assessment Score in Prognosticating sick Children in Paediatric Intensive care Unit - Kafle, Raju; Sanjeev, Shah; Binod Kumar, Gupta (Journal of Nepal Paediatric Society, 2022)
Introduction: There are number of scoring systems to assess the morbidity and mortality of sick children in intensive care unit. Out of these scoring systems our study was designed to look for the utility of Sequential Organ Failure Assessment (SOFA) score which is less time consuming and simple to apply as a predictor of mortality in sick children admitted in Paediatric Intensive Care Unit (PICU). Methods: This was a prospective observational study done in PICU of Universal College of Medical Sciences, Bhairahawa, Nepal. Recruited patients were all critically sick children above one year who stayed in hospital above 72 hours and underwent all necessary evaluation, and were followed up until they were discharged or deceased. Initial SOFA score was calculated within 24 hours of admission (SOFA T0) and again calculated after 72 hours (SOFA T72). Delta SOFA score was calculated as the change in SOFA scores over 72 hours (SOFA T0 - SOFA T72). The primary outcome was in-hospital mortality. Results: When compared to outcome, the non survivors had high mean initial SOFA (T0) 11.51 ± ences ec ing 3.001 (P < 0.001), mean SOFA after 72 hours (T72) was 15.51 ± 4.026 (P < 0.001) and mean delta SOFA (T0-T72) was 4.58 ± 2.59 (P = 0.166) as compared to survivors. Delta SOFA was not significantly associated with outcome (P = 0.166). The initial SOFA score T0 > / = 11 predicted a mortality of 70.90% and SOFA T72 score of >/=15 predicted a mortality of 81.60% but delta sofa >/= 4 predicts a mortality of only 43.60%. Area under receiver operating characteristic (ROC) curve for SOFA TO was 0.769, for SOFA T72 was 0.890 and for delta SOFA was 0.604 and thus, showing excellent discriminative power for SOFA 72 for predicting mortality. Conclusions: The SOFA score demonstrated fair to good accuracy for predicting mortality when applied to sick children > 1 year admitted in PICU. Our study showed both initial SOFA T0 and SOFA at 72 hours predict mortality with good accuracy but SOFA at 72 hours is a better predictor of mortality as compared to initial and delta SOFA scores.